The French Colonial Land Policy in Algeria at the Beginning of the Occupation (1830–1846) - Boughedada, Dr. El-Amir; Ayada, Dr. Ali (Journal of Ecohumanism, 2025)
After only a few months of entering Algiers, the French colonial administration assigned great importance to land. It turned land into a central pillar of its economic system. In the nineteenth century, land ownership served as the only legal and economic framework that enabled settler colonialism. At the same time, most Europeans who came to settle between 1830 and 1846 did not possess sufficient capital to enter trade or industry. Agriculture appeared to them as the only viable activity once they obtained land free of charge. The main motives that pushed migrants to come were the desire to gain wealth, whether by exploiting farms or through land speculation.Yet colonial land policy was inconsistent. From the moment France entered Algeria, it sought to secure suitable lands for settlers. To do so, it created a state domaine to replace the former beylik domain. French law was then applied to property in Algeria, especially to vacant lands, as well as to the estates of the deys, beys, and Ottoman officials. It later extended to the lands of Algerians who had left the country with Emir Abdelkader or with the Ottomans, or who were forced into exile. Added to this was the effort of the French authorities to impose French land legislation with two aims: to “Frenchify” land and to ease the process of seizing it and selling it.